A Review of Customary Law and Islamic Law on Marriage of Couples Motivated by Behavior Violating Norms - Prayetno, Dwi (El-Sirry: Jurnal Hukum Islam dan Sosial, 2025)
This study aims to examine the practice of marriage motivated by behavior that violates norms, both from the perspective of customary law and Islamic law. This phenomenon is often found in various communities, especially when couples who commit social offenses, such as extramarital relationships, are then "married" as a form of problem solving. In the traditional context, this kind of marriage is often seen as a way of preserving family honor and restoring a disturbed social order. Meanwhile, from the perspective of Islamic law, marriage is not merely a solution to transgression, but must meet the legal requirements and principles of sincerity, and place repentance as an important moral requirement. Using a qualitative approach and literature study, this study analyzes how both legal systems—customary and Islamic—view, respond, and shape norms for these practices. The results of the study show that there is a common point between customary law and Islamic law in maintaining social stability, but there are also differences in the emphasis on the moral aspects and legality of marriage. This study recommends the need for constructive dialogue between traditional stakeholders and religious leaders in formulating a more equitable and educational approach for the younger generation in facing the dynamics of social change